Release film

By performing surface treatment on the release layer of the release film to reduce its bromine penetration Z value, the problem of high force and prone to defects during the release film detachment in the RtoR manufacturing method is solved, and better release performance and production stability are achieved.

JP2025061764APending Publication Date: 2025-04-11SEKISUI CHEMICAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2025009804
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2019-09-25
Filing Date
2025-01-23
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

In the roll-to-roll (RtoR) manufacturing method, the traditional release film is prone to low shear angle after it is detached from the flexible circuit board, resulting in a large force required to be applied during the disengagement, which is prone to defects.

Method used

A release film with a low bromine penetration Z value was used. The film showed that its bromine penetration Z value was 4 or lower by the bromine glue-containing permeability test. Its release performance was further improved by surface treatment on the surface of the release layer, such as flame treatment or friction treatment.

Benefits of technology

The release performance of the release film is improved, the force required during disengagement is reduced, the defect incidence is reduced, and it is suitable for RtoR manufacturing methods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025061764000001
    Figure 2025061764000001
  • Figure 2025061764000002
    Figure 2025061764000002
  • Figure 2025061764000003
    Figure 2025061764000003
Patent Text Reader

Abstract

To provide a release film that has better releasability than a conventional film and can be suitably used in a manufacture of a flexible circuit board by a roll-to-roll method.SOLUTION: A release film has at least one release layer, and has a bromine permeability Z of 4 or less as measured by a bromine-containing adhesive penetration test described below. Bromine-Containing Adhesive Penetration Test) An adhesive surface of a coverlay film having a bromine compound as an adhesive component and a release layer of the release film are brought into contact with each other, and then heat pressed under conditions of a pressure of 30 kgf, at 180°C, and for 5 minutes. The coverlay film is then peeled off, and a bromine penetration rate Z is calculated according to the following formula (1). Z=Σ{A(i) / B(i)} (1) In formula (1), A(i) and B(i) respectively represent Br-fragment intensity and total fragment intensity in the i-th measurement of time-of-flight secondary ion mass spectrometry, and i represents an integer from 1 to 100.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a release film. [Background technology]

[0002] 2. Description of the Related Art Release films are used in the manufacturing processes of printed wiring boards, flexible circuit boards, multilayer printed wiring boards, and the like. In the manufacturing process of a flexible circuit board, a coverlay film is heat-pressed and bonded to a flexible circuit board body on which a copper circuit is formed via a thermosetting adhesive or a thermosetting adhesive sheet. At this time, by disposing a release film between the coverlay film and the heat-press plate, it is possible to prevent the coverlay film and the heat-press plate from adhering to each other, and also to prevent problems such as the adhesive seeping out and interfering with the plating process of the electrode portion (for example, Patent Documents 1 and 2).

[0003] In recent years, release films made of multiple layers including a release layer and a cushion layer have been used to ensure performance such as releasability and ability to conform to unevenness (embedding ability) in response to the thinning of L / S (line / space) on flexible circuit boards. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Application Publication No. 5-283862 [Patent Document 2] JP 2009-132806 A Summary of the Invention [Problem to be solved by the invention]

[0005] In recent years, as flexible circuit boards become thinner, release films are required to have further improved releasability. In addition, in recent years, the manufacturing of flexible circuit boards has also become automated using the roll-to-roll (RtoR) method and the like. In the RtoR method, the flexible circuit board body and release film, etc., which are unwound from a roll, are transported between heat press plates, heat press bonded, and then wound up on the roll again. In such an RtoR method, when the release film is peeled off from the flexible circuit board after heat press bonding, the peel angle tends to be low. Therefore, when a conventional release film is used, a larger force may need to be applied during peeling, which may lead to defects. Therefore, release films are required to have further improved releasability.

[0006] An object of the present invention is to provide a release film which has better releasability than conventional films and can be suitably used in the production of flexible circuit boards by the roll-to-roll method. [Means for solving the problem]

[0007] The present invention is a release film having at least one release layer, which has a bromine permeability Z of 4 or less as measured by the following bromine-containing adhesive penetration test. (Bromine-containing adhesive penetration test) The adhesive surface of a coverlay film having a bromine compound as an adhesive component is brought into contact with the release layer of the release film, and then heat pressed under conditions of a pressure of 30 kgf, 180°C, and 5 minutes. The coverlay film is then peeled off, and the bromine penetration rate Z is calculated using the following formula (1).

[0008]

number

[0009] In formula (1), A(i) and B(i) are the Br -and total fragment intensity, where i represents an integer from 1 to 100. The present invention will be described in detail below.

[0010] The heat pressing process in the manufacture of flexible circuit boards may be performed at a temperature of 160 to 180°C for the purpose of softening and hardening the adhesive. The present inventors have found that in the temperature range corresponding to the softening and hardening of the adhesive, the adhesive component of the coverlay film to be laminated permeates into the release layer of the release film, and the permeated adhesive component brings about an anchor effect, so that adhesive force is generated between the release film and the adhesive of the coverlay film. As a result of further intensive research, it has been found that the releasability can be improved by controlling the permeation of the adhesive into the release layer of the release film, and the present invention has been completed.

[0011] The release film of the present invention has at least one release layer. The release film of the present invention has a bromine penetration degree Z of 4 or less, as measured by the following bromine-containing adhesive penetration test. The release film of the present invention can exhibit high releasability when the bromine penetration degree Z value is 4 or less. The bromine penetration degree Z value is preferably 3.5 or less, more preferably 3 or less, even more preferably 2.5 or less, and particularly preferably 1.0 or less. The lower limit of the bromine penetration degree Z value is not particularly limited, and may be 0.

[0012] Specifically, the bromine-containing adhesive penetration test is carried out as follows: First, a coverlay film having a bromine compound as an adhesive component is prepared. With the adhesive surface of the coverlay film in contact with the release layer of the release film, a heat press is performed at a pressure of 30 kgf, 180°C, and 5 minutes. The coverlay film may be a coverlay film having a general adhesive layer used in the manufacturing process of flexible circuit boards, specifically, for example, commercially available products such as "CISV-1215", "CISV-1225", "CISV-2525", and "CISV-2535" manufactured by Nikkan Kogyo Co., Ltd. The above heat pressing conditions are in accordance with the heat pressing conditions used in a general manufacturing process for flexible circuit boards.

[0013] In the above bromine-containing adhesive penetration test, the coverlay film is then peeled off from the release film after the heat press. The peeling method is not particularly limited, but an example of such a method is to cut a sample to a length of 125 mm and a width of 25 mm, and then peel the coverlay film from the release film at an angle of 180° at a speed of 500 mm / min.

[0014] In the above bromine-containing adhesive penetration test, the surface of the release layer after the coverlay film is peeled off is then analyzed by time-of-flight secondary ion mass spectrometry. Time-of-Flight Secondary Ion Mass Spectrometry (TOF-SIMS) is a method in which a solid sample is irradiated with an ion beam (primary ions) and the ions (secondary ions) emitted from the surface are mass-separated using their flight time difference (flight time is proportional to the square root of weight). TOF-SIMS can obtain information on elements and molecular species present at a depth of 1 nm or less from the sample surface with high detection sensitivity. Examples of analytical instruments used in TOF-SIMS include commercially available products such as "TOF-SIMS Type 5" manufactured by ION TOF. Using a TOF-SIMS analyzer, Br from the adhesive of the coverlay film remaining on the release layer surface was - In the present invention, the fragment intensity of the sample and the total fragment intensity are measured. - The fragment intensity measurements are repeated alternately.

[0015] Sputtering involves introducing an inert gas such as argon into a vacuum, applying a negative voltage to the target to generate a glow discharge, ionizing the inert gas atoms, and causing the gas ions to collide with the target surface at high speed, striking it violently. This can grind the target surface to a depth on the order of nanometers to micrometers. Specifically, for example, C60 + By performing sputtering using a sputtering agent while adjusting conditions such as voltage, it is possible to dig into the surface of the release layer at a depth of 1 nm per sputtering. Therefore, with this method, it is possible to dig into the release film to a depth of 100 nm by performing sputtering 100 times, for example.

[0016] An example of the TOF-SIMS analysis conditions and sputtering conditions in the bromine-containing adhesive penetration test is shown below. Equipment: ION TOF "TOF-SIMS 5" Primary ion: 209Bi 3++ Primary ion voltage: 25kV Primary ion current: 1pA Mass range: 1 to 500 mass Analysis area: 500μm×500μm□ Charge prevention: Electron irradiation neutralization Sputter ion: C60 + Sputter ion voltage: 20keV Sputter ion current: 1nA Sputter area: 800μm×800μm□ Number of sputters: 99

[0017] In the above-mentioned bromine-containing adhesive penetration test, the release layer is etched in the depth direction while performing measurements by time-of-flight secondary ion mass spectrometry multiple times. -The fragment intensity of the sample is designated as A(i) and the total fragment intensity is designated as B(i), and the value of "A(i) / B(i)" is calculated for each measurement. The integrated value of A(i) / B(i) over all measurements, that is, the bromine penetration depth Z calculated by the above formula (1), is the bromine penetration depth Z of the sample up to the surface layer of the release layer (approximately i x 1 nm deep). - The smaller the bromine penetration rate Z, the more difficult it is for the adhesive of the coverlay film to penetrate into the release film during the heat pressing step in the manufacture of flexible circuit boards.

[0018] The method of making the bromine penetration rate Z value 4 or less is not particularly limited, but includes subjecting the surface of the release layer to a surface treatment. The surface treatment is not particularly limited, and includes, for example, flame treatment or friction treatment. These surface treatments may be used alone or in combination. In particular, a method of subjecting the surface of the release layer to a friction treatment after adjusting the surface to be smooth (small arithmetic mean roughness Ra) or high gloss, or a method of subjecting the surface of the release layer to a flame treatment is effective. Among them, flame treatment is preferable because it can efficiently treat only the surface of the release layer and can efficiently treat the surface without being affected by the state of the release layer during treatment (surface roughness of the release layer during treatment).

[0019] The reason why the odor penetration rate Z can be reduced by friction or flame treatment is not clear, but it can be assumed as follows. It is considered that the anchor effect of the adhesive is particularly affected on the outermost surface (approximately 0.1 to 1 μm region) of the release layer. It is considered that friction or flame treatment exerts some action (for example, increasing the crystallinity) on the molecules of the outermost surface, and the molecules on the surface are strongly bound and the free volume of the molecules is reduced, making it difficult for the adhesive component to penetrate from the surface to the inside. In addition, the reason why friction on a smooth or highly glossy surface is effective can be assumed as follows. When the arithmetic mean roughness Ra is relatively large, some physical property changes or uniform processing may be hindered due to the unevenness of the release layer surface during friction. On the other hand, when the arithmetic mean roughness Ra is sufficiently small, it is considered that the physical property changes and uniform processing hindered due to the unevenness of the release layer surface are small, and the surface can be sufficiently changed by friction treatment. Furthermore, since smooth gloss is affected by the surface roughness of the object and the size of the crystal grains inside, a high gloss means a low surface roughness and small crystal grains (below a certain size). When the crystal grains are relatively large, multiple crystal grains become three-dimensional obstacles to each other, hindering the growth of crystals due to surface treatment. On the other hand, when the crystal grains are relatively small, the crystal growth is promoted without the above-mentioned three-dimensional obstacles, and as a result, it is thought that the effect of reducing odor penetration Z is improved. It is also thought that the size of the crystal grains is affected by the cooling and elongation stress during melt extrusion. According to the investigations of the present inventors, it was difficult to sufficiently reduce the odor permeability Z even if a friction treatment was performed on a surface that was neither smooth nor highly glossy.

[0020] The flame treatment is a treatment in which the surface of the release layer is directly heated with a flame using a gas burner or the like. The conditions of the flame treatment are not particularly limited, but specifically, for example, a method can be mentioned in which the surface of the release layer is directly burned with a flame using a gas burner using propane gas (LPG) as fuel gas while feeding the film at a constant speed, with a gas flow rate of 5 L / min, an air flow rate of 125 L / min, and a nozzle-to-sample distance of 150 mm. At this time, the degree of flame treatment can be controlled by adjusting the film feeding speed.

[0021] The method for adjusting the surface of the release layer to be smooth is not particularly limited, but when melt-extruding the resin constituting the release layer and cooling the molten resin, it is preferable to adopt, for example, the following method. That is, a method of using a cooling roll having a smoother surface and transferring the roll surface shape to the film, or a method of adjusting the elongation stress applied to the molten resin during cooling is preferable. The arithmetic mean roughness Ra of the release layer before the friction treatment can be, for example, 0.50 μm or less. From the viewpoint of reducing the odor permeability Z, it is sufficient that the surface of the release layer is smooth at the time of the friction treatment. After the friction treatment, even if the surface of the release layer is embossed to increase the arithmetic mean roughness Ra, the odor permeability Z itself is not significantly affected.

[0022] The release layer preferably has an arithmetic mean roughness Ra of 0.5 μm or more on the surface. By having the arithmetic mean roughness Ra of 0.5 μm or more on the surface of the release layer, when the release film is placed between the coverlay film and the heat press plate, air bubbles are prevented from being entrapped at the interface, and wrinkle resistance can be improved. The arithmetic mean roughness Ra of the surface of the release layer is more preferably 1 μm or more, even more preferably 2 μm or more, and particularly preferably 3 μm or more. The upper limit of the arithmetic mean roughness Ra of the surface of the release layer is not particularly limited, but from the viewpoint of releasability, it is preferably 20 μm or less, and more preferably 15 μm or less. As described above, when flame treatment is performed, the bromine permeability Z can be reduced regardless of the arithmetic mean roughness Ra of the surface of the release layer at the time of flame treatment. Therefore, a release film having excellent wrinkle resistance while exhibiting high releasability can be obtained.

[0023] The method for increasing the arithmetic mean roughness Ra of the release layer is not particularly limited, but when the resin constituting the release layer is melt-extruded and the molten resin is cooled, the following method can be adopted, for example. That is, a method of using a cooling roll having an uneven surface to transfer the roll surface shape to the film, or a method of adjusting the elongation stress applied to the molten resin during cooling to be small, etc. are preferable. In addition, an embossing roll can be used to emboss the surface of the film by a general method.

[0024] The release layer has a preferred lower limit of the overall crystallinity of 25% and a preferred upper limit of 50%. If the crystallinity of the entire release layer is increased more than necessary, the flexibility of the entire release film is reduced, and the ability to follow unevenness is reduced, which may cause voids during heat press bonding or increase the width of the adhesive seeping out. By adjusting the crystallinity of the entire release layer, the release film of the present invention has excellent releasability and ability to follow unevenness. If the crystallinity of the entire release layer is 25% or more, the heat resistance of the release film is improved. If the crystallinity of the entire release layer is 50% or less, the ability to follow unevenness of the release film is improved. The lower limit of the crystallinity of the entire release layer is more preferably 30%, and even more preferably 35%. The upper limit of the crystallinity of the entire release layer is more preferably 45%, even more preferably 40%, and particularly preferably 35%.

[0025] The crystallinity of the entire release layer can be calculated by plotting a baseline on a diffraction measurement plot obtained by analyzing the entire release layer by wide-angle X-ray diffraction, fitting the crystalline phase and the amorphous phase, and calculating the crystallinity of the entire release layer from the total peak area of ​​the crystalline phase and the total peak area of ​​the amorphous phase according to the following formula (2). When the release film is made of multiple layers, each layer of the release film is peeled off and a sample consisting of only the release layer is analyzed, thereby evaluating the crystallinity of the entire release layer.

[0026]

number

[0027] As an X-ray diffraction apparatus for determining the degree of crystallinity of the entire release layer, for example, a horizontal sample type X-ray diffraction apparatus for thin film evaluation (Smart Lab) manufactured by Rigaku Corporation set under the following conditions can be used. X-ray source CuKα radiation Tube voltage-tube current 45kV-200mA Input optical system Focusing method Measurement range: 5-80° Measurement interval: 0.02° Scanning speed: 5.0° / min Scanning method Out-of-Plane method

[0028] The method of adjusting the crystallinity of the entire release layer to the above range is not particularly limited, but when melt-extruding the resin constituting the release layer and cooling the molten resin, it is preferable to adopt, for example, the following method. That is, a method of adjusting the contact time between the molten resin and the cooling roll, a method of adjusting the cooling roll temperature, etc. are preferable. In this way, by adjusting the temperature gradient between the surface of the release layer and the inside of the release layer, the crystallization speed on the surface of the release layer and the inside of the release layer can be adjusted, and the crystallinity of the entire release layer can be adjusted. The crystallinity of the entire release layer can also be adjusted to a value higher than the crystallinity of the extreme surface of the release layer.

[0029] The release layer preferably contains a polyester resin. This improves the releasability of the release film. In particular, the release layer preferably contains an aromatic polyester resin, because it has excellent conformability to unevenness and excellent resistance to bleeding of the adhesive formed on the coverlay film.

[0030] The aromatic polyester resin is not particularly limited, but crystalline aromatic polyester resin is preferred.Specific examples include polyethylene terephthalate resin, polybutylene terephthalate resin, polyhexamethylene terephthalate resin, polyethylene naphthalate resin, polybutylene naphthalate resin, terephthalic acid butanediol polytetramethylene glycol copolymer, etc.These aromatic polyester resins may be used alone or in combination of two or more.Among them, polybutylene terephthalate resin is preferred from the viewpoint of balance of heat resistance, releasability, conformability to unevenness, etc. Also preferred is a mixed resin of a polybutylene terephthalate resin and a block copolymer of polybutylene terephthalate and an aliphatic polyether. The aliphatic polyether is not particularly limited, and examples thereof include polyethylene glycol, polydiethylene glycol, polypropylene glycol, and polytetramethylene glycol.

[0031] From the viewpoint of film forming properties, the aromatic polyester resin has a melt volume flow rate of 30 cm 3 / 10min or less is preferable, and 20cm 3 It is more preferable that the melt volume flow rate is equal to or less than 1000000 / min. The melt volume flow rate can be measured in accordance with ISO1133 at a measurement temperature of 250° C. and a load of 2.16 kg.

[0032] Among the above aromatic polyester resins, commercially available examples include "Pelprene (registered trademark)" (manufactured by Toyobo Co., Ltd.), "Hytrel (registered trademark)" (manufactured by DuPont-Toray Co., Ltd.), "Duranex (registered trademark)" (manufactured by Polyplastics Co., Ltd.), and "Novaduran (registered trademark)" (manufactured by Mitsubishi Engineering Plastics Corporation).

[0033] The release layer may contain a mixed resin containing polybutylene terephthalate resin and an elastomer. The elastomer is not particularly limited, and may be, for example, a block copolymer of polybutylene terephthalate and an aliphatic polyether. The aliphatic polyether is not particularly limited, and may be, for example, polyethylene glycol, polydiethylene glycol, polypropylene glycol, polytetramethylene glycol, etc.

[0034] The proportion of the polybutylene terephthalate resin in the resin constituting the release layer is not particularly limited, but is preferably 75% by weight or more. If the proportion of the polybutylene terephthalate resin is 75% by weight or more, the release property of the release film is improved. A more preferable lower limit of the proportion of the polybutylene terephthalate resin in the resin constituting the release layer is 80% by weight.

[0035] The release layer may contain a rubber component. When the release layer contains a rubber component, the ability to conform to the irregularities of the release film is improved. The rubber component is not particularly limited, and examples thereof include natural rubber, styrene-butadiene copolymer, polybutadiene, polyisoprene, acrylonitrile-butadiene copolymer, ethylene-propylene copolymer (EPM, EPDM), polychloroprene, butyl rubber, acrylic rubber, silicone rubber, urethane rubber, etc. Examples of the rubber component include olefin-based thermoplastic elastomer, styrene-based thermoplastic elastomer, vinyl chloride-based thermoplastic elastomer, ester-based thermoplastic elastomer, amide-based thermoplastic elastomer, etc.

[0036] The release layer may contain a stabilizer. The stabilizer is not particularly limited, and examples thereof include hindered phenol-based antioxidants and heat stabilizers. The hindered phenol-based antioxidant is not particularly limited, and examples thereof include 1,3,5-trimethyl-2,4,6-tris(3,5-di-t-butyl-4-hydroxybenzyl)benzene, 3,9-bis{2-[3-(3-t-butyl-4-hydroxy-5-methylphenyl)-propionyloxy]-1,1-dimethylethyl}-2,4,8,10-tetraoxaspiro[5,5]undecane, and the like. The heat stabilizer is not particularly limited, and examples thereof include tris(2,4-di-t-butylphenyl)phosphite, trilauryl phosphite, 2-t-butyl-α-(3-t-butyl-4-hydroxyphenyl)-p-cumenylbis(p-nonylphenyl)phosphite, dimyristyl 3,3'-thiodipropionate, distearyl 3,3'-thiodipropionate, pentaerythryl tetrakis(3-laurylthiopropionate), ditridecyl 3,3'-thiodipropionate, and the like.

[0037] The release layer may further contain conventionally known additives such as fibers, inorganic fillers, flame retardants, ultraviolet absorbing agents, antistatic agents, inorganic substances, and salts of higher fatty acids.

[0038] The thickness of the release layer is not particularly limited, but the preferred lower limit is 10 μm, and the preferred upper limit is 40 μm. If the thickness of the release layer is 10 μm or more, the heat resistance of the release film is improved. If the thickness of the release layer is 40 μm or less, the conformability of the release film to the unevenness is improved. The more preferred lower limit of the thickness of the release layer is 15 μm, and the more preferred upper limit is 30 μm.

[0039] The release film of the present invention may have a single-layer structure constituted only of the release layer, or may have a multi-layer structure containing layers other than the release layer.

[0040] The release film of the present invention preferably further comprises a cushion layer, which improves the ability of the release film to conform to unevenness. When the cushion layer is included, the release film of the present invention may have at least one release layer and a cushion layer, and may have a two-layer structure or a three-layer structure or more. In particular, it is preferable to have a structure having a release layer on both sides of the cushion layer. In this case, the release layers on both sides may have the softening temperature as described above, or only the release layer on one side may have the softening temperature as described above. In addition, the release layers on both sides may have the same resin composition or different resin compositions. In addition, the release layers on both sides may have the same thickness or different thicknesses. Furthermore, the release film of the present invention may have a structure in which the release layer and the cushion layer are in direct contact with each other and integrated together, or may have a structure in which the release layer and the cushion layer are integrated together via an adhesive layer.

[0041] The resin constituting the cushion layer is not particularly limited, but it is preferable that the cushion layer contains the resin constituting the release layer. The cushion layer contains the resin constituting the release layer, so that the adhesion between the release layer and the cushion layer is improved. The cushion layer more preferably contains the main component resin of the release layer, and further preferably contains the main component resin of the release layer and a polyolefin resin. Here, the main component resin of the release layer means the resin with the highest content among the resins contained in the release layer.

[0042] The content of the resin constituting the release layer in the cushion layer is not particularly limited, but the preferred lower limit is 10% by weight, and the preferred upper limit is 50% by weight. If the content of the resin constituting the release layer is 10% by weight or more, the adhesion between the release layer and the cushion layer is improved. If the content of the resin constituting the release layer is 50% by weight or less, the flexibility of the cushion layer is sufficient, and the ability to follow the unevenness of the release film is improved. The more preferred lower limit of the content of the resin constituting the release layer is 20% by weight, and the even more preferred lower limit is 25% by weight. The more preferred upper limit of the content of the resin constituting the release layer is 40% by weight, and the even more preferred upper limit is 35% by weight.

[0043] The polyolefin resin is not particularly limited, and examples thereof include polyethylene resins (e.g., high-density polyethylene, low-density polyethylene, linear low-density polyethylene), polypropylene resins, ethylene-vinyl acetate copolymers, etc. Also included are ethylene-acrylic monomer copolymers such as ethylene-methyl methacrylate copolymers, ethylene-ethyl acrylate copolymers, and ethylene-acrylic acid copolymers. These polyolefin resins may be used alone or in combination of two or more. Among them, polypropylene resins are preferred because they easily achieve both conformability to irregularities and heat resistance.

[0044] The content of the polyolefin resin in the cushion layer is not particularly limited, but the preferred lower limit is 50% by weight, and the preferred upper limit is 90% by weight. If the content of the polyolefin resin is 50% by weight or more, the flexibility of the cushion layer is sufficient, and the ability to follow the unevenness of the release film is improved. If the content of the polyolefin resin is 90% by weight or less, the adhesion between the release layer and the cushion layer is improved. The more preferred lower limit of the content of the polyolefin resin is 60% by weight, and even more preferred lower limit is 65% by weight. The more preferred upper limit of the content of the polyolefin resin is 80% by weight, and even more preferred upper limit is 75% by weight.

[0045] The cushion layer may further contain a resin such as polystyrene, polyvinyl chloride, polyamide, polycarbonate, polysulfone, or polyester. The cushion layer may further contain additives such as fibers, inorganic fillers, flame retardants, ultraviolet absorbing agents, antistatic agents, inorganic substances, and salts of higher fatty acids.

[0046] The cushion layer may have a single-layer structure made of a single layer, or a multi-layer structure made of a laminate of multiple layers. When the cushion layer has a multi-layer structure, the multiple layers may be laminated together via an adhesive layer.

[0047] The thickness of the cushion layer is not particularly limited, but the preferred lower limit is 15 μm, and the preferred upper limit is 200 μm. If the thickness of the cushion layer is 15 μm or more, the ability to follow the unevenness of the release film is improved. If the thickness of the cushion layer is 200 μm or less, the exudation of resin from the cushion layer that occurs at the film end during heat press bonding can be suppressed. The more preferred lower limit of the thickness of the cushion layer is 30 μm, and the more preferred upper limit is 150 μm.

[0048] The method for producing the release film of the present invention is not particularly limited, and examples thereof include a method in which a film is first prepared by a water-cooled or air-cooled coextrusion inflation method, a coextrusion T-die method, a solvent casting method, a hot press molding method, or the like, and then the above-mentioned surface treatment is performed. In the case of a structure having the release layers on both sides of the cushion layer, a method of preparing a film to be one of the release layers, laminating the cushion layer on this film by extrusion lamination, and then dry laminating the other release layer can be used. Also, a method of dry laminating the film to be one of the release layers, the film to be the cushion layer, and the film to be the other release layer can be used. Among these, the co-extrusion T-die method is preferred because it allows excellent control of the thickness of each layer. By subjecting the thus obtained film to the above-mentioned surface treatment, the bromine permeability Z can be adjusted to 4 or less.

[0049] The use of the release film of the present invention is not particularly limited, but it can be suitably used in the production processes of printed wiring boards, flexible circuit boards, multilayer printed wiring boards, and the like. Specifically, for example, in the manufacturing process of a flexible circuit board, the release film of the present invention can be used when hot press bonding a coverlay film to a flexible circuit board main body having a copper circuit formed thereon via a thermosetting adhesive or a thermosetting adhesive sheet. Since the release film of the present invention has extremely excellent releasability, it can also be suitably used in the production of flexible circuit boards by the RtoR method, which requires high releasability. Effect of the Invention

[0050] According to the present invention, it is possible to provide a release film which has better releasability than conventional ones and can be suitably used in the production of flexible circuit boards by the roll-to-roll method. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0051] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0052] Example 1 (1) Preparation of films Polybutylene terephthalate resin (PBT) was used as the resin constituting the release layers (release layers a and b). A mixed resin of 60 parts by weight of low melting point polypropylene resin (LDPE) and 40 parts by weight of polybutylene terephthalate resin (PBT) (main component resin of the release layer) was used as the resin constituting the cushion layer. The resin constituting the release layer and the resin constituting the cushion layer were three-layer co-extruded at a T-die width of 400 mm using an extruder (GM Engineering, GM30-28 (screw diameter 30 mm, L / D 28)), and the extruded molten resin was cooled by a cooling roll (temperature 50°C). This resulted in a three-layer film having a release layer a (thickness 25 μm) and a release layer b (thickness 25 μm) on both sides of the cushion layer (thickness 50 μm). During cooling, the contact time between the molten resin and the cooling roll was 2.5 seconds, and the elongation stress when cooling the molten resin by the cooling roll was 140 kPa.

[0053] The above tensile stress is expressed by the following formula (3).

[0054]

number

[0055] The strain rate and the elongational viscosity of the molten resin are expressed by the following formulas (4) and (5), respectively.

[0056]

number

[0057] In equation (4), V is the roll speed (m / s), V0 is the flow velocity of the molten resin at the die exit (m / s), and L is the distance from the die exit to the point where the molten resin contacts the roll (m).

[0058] (2) Film surface treatment The embossed film was transported on a roll at a speed of 15 m / min, while a gas burner using propane gas (LPG) as the fuel gas was used to directly heat the surface of release layer a with a flame from a nozzle-to-sample distance of 150 mm at a gas flow rate of 5 L / min and an air flow rate of 125 L / min, to obtain a release film.

[0059] (3) Bromine-containing adhesive penetration test The release layer a of the obtained release film was brought into contact with the adhesive surface of a coverlay film ("CISV-2535" manufactured by Nikkan Industries Co., Ltd.) and heat-pressed at a pressure of 30 kgf and 180°C for 5 minutes. Next, the release film after heat pressing was cut to a length of 125 mm x width of 25 mm, and the coverlay film was peeled off from the release film at a speed of 500 mm / min at an angle of 180°.

[0060] The release layer a after the coverlay film was peeled off was analyzed by time-of-flight secondary ion mass spectrometry (TOF-SIMS). The TOF-SIMS analysis conditions and sputtering conditions were as follows. Equipment: ION TOF "TOF-SIMS 5" Primary ion: 209Bi 3++ Primary ion voltage: 25kV Primary ion current: 1pA Mass range: 1 to 500 mass Analysis area: 500μm×500μm□ Charge prevention: Electron irradiation neutralization Sputter ion: C60 + Sputter ion voltage: 20keV Sputter ion current: 1nA Sputter area: 800μm×800μm□ Number of sputters: 99 Under the above conditions, sputtering was performed 100 times in the depth direction of the release layer a, while performing TOF-SIMS analysis, and the value of the bromine penetration rate Z was calculated according to the above formula (1).

[0061] (4) Measurement of crystallinity of entire release layer a Each layer of the release film was peeled off to obtain a sample consisting of only the release layer a. The release layer a was analyzed by wide-angle X-ray diffraction. A linear baseline was drawn in the range of 2θ=12.0 to 28.18° on the obtained diffraction measurement plot. The crystalline phase and the amorphous phase were each fitted as a Gaussian function, and the crystallinity of the entire release layer was calculated from the obtained total peak area of ​​the crystalline phase and the total peak area of ​​the amorphous phase according to the above formula (2).

[0062] As the wide-angle X-ray diffraction device, a horizontal sample type X-ray diffraction device for thin film evaluation (Smart Lab) manufactured by Rigaku Corporation was used, which was set under the following conditions. X-ray source CuKα radiation Tube voltage: 45kV-200mA Input optical system Focusing method Measurement range: 5-80° Measurement interval: 0.02° Scanning speed: 5.0° / min Scanning method Out-of-Plane method

[0063] (Examples 2 to 7) A release film was obtained in the same manner as in Example 1, except that the contact time between the molten resin and the cooling roll, the cooling roll temperature and elongation stress, and the flame treatment conditions were changed as shown in Table 1. For the obtained release film, the arithmetic mean roughness Ra of the surface was measured, a bromine-containing adhesive penetration test was performed, and the crystallinity of the entire release layer a was measured in the same manner as in Example 1.

[0064] Example 8 Polymethylpentene resin (TPX) was used as the resin constituting the release layers (release layers a and b). A mixed resin of 50 parts by weight of low melting point polypropylene resin (LDPE) and 50 parts by weight of polymethylpentene resin (TPX) (main component resin of the release layer) was used as the resin constituting the cushion layer. The resin constituting the release layer and the resin constituting the cushion layer were three-layer co-extruded at a T-die width of 400 mm using an extruder (GM Engineering, GM30-28 (screw diameter 30 mm, L / D 28)), and the extruded molten resin was cooled by a cooling roll (temperature 70°C). This resulted in a three-layer film having a release layer a (thickness 25 μm) and a release layer b (thickness 25 μm) on both sides of the cushion layer (thickness 50 μm). During cooling, the contact time between the molten resin and the cooling roll was 1.0 second, and the elongation stress when cooling the molten resin by the cooling roll was 190 kPa. The obtained film was subjected to flame treatment under the conditions shown in Table 1 in the same manner as in Example 1 to obtain a release film. For the obtained release film, the arithmetic mean roughness Ra of the surface was measured, a bromine-containing adhesive penetration test was performed, and the crystallinity of the entire release layer a was measured in the same manner as in Example 1.

[0065] (Comparative Examples 1 to 4) A release film was obtained in the same manner as in Example 1, except that the contact time between the molten resin and the cooling roll, the cooling roll temperature and elongation stress, and the surface treatment method were changed as shown in Table 2. For the obtained release film, the arithmetic mean roughness Ra of the surface was measured, a bromine-containing adhesive penetration test was performed, and the crystallinity of the entire release layer a was measured in the same manner as in Example 1. In Comparative Examples 1 and 2, the friction treatment was performed by feeding the obtained film with a roll, and using a friction treatment device (Yamagata Kikai Co., Ltd. polishing device, model YCM-150M) to the surface of the release layer a, and using a woven fabric as the surface material of the friction treatment material. During the friction treatment, a surface treatment roll was provided between the feed roll and the take-up roll, and the surface treatment roll was pressed against the film to apply a load to the film. The amount of work energy applied during the friction treatment was 200 kJ. In addition, in Comparative Example 3, the stretching treatment was performed by preheating the obtained film at 75°C for 1 minute using a batch-type biaxial stretching machine, and then simultaneously biaxially stretching the film at 75°C at a stretching speed of 50 mm / s to 2 times the original length and 2 times the original width, and then heat-setting the film in a hot air oven heated to 190°C for 10 seconds.

[0066] (evaluation) The release films obtained in the examples and comparative examples were evaluated by the following methods. The results are shown in Tables 1 and 2.

[0067] (1) Evaluation of releasability CVL1 ("CISV-2535" manufactured by Nikkan Industries Co., Ltd.) was used as the epoxy adhesive sheet, and the release film was placed on the epoxy adhesive sheet so that the release layer a was in contact with the epoxy adhesive sheet, and the sheet was then heated at 180°C and 30 kgf / cm 2The samples were heat pressed for 5 minutes under the above conditions. After that, the release film peeled off naturally from some of the samples. For samples in which the release film did not peel off naturally even after 10 minutes had passed since the heat press, the samples were cut to a width of 30 mm and subjected to a peel test at a test speed of 500 mm / min and a peel angle of 30° to determine the 30° peel strength (30° peel value). In addition, in order to compare the releasability under conditions more severe than those normally required, the same measurements were carried out, replacing the epoxy adhesive sheet CVL1 with CVL2 ("HXC2525" manufactured by DuPont), an epoxy adhesive sheet with stronger adhesive strength. Based on these measurement results, the releasability of the release film was evaluated as follows. ◎: When the release film peeled off naturally in the test using CVL1, and when the 30° peel strength was 100gf / cm or less in the test using CVL2 ○: In the test using CVL1, the release film peeled off naturally, and in the test using CVL2, the 30° peel strength was greater than 100 gf / cm. ×: When the release film did not peel off naturally in the test using CVL1

[0068] In addition, a peel test conducted at a peel angle of 30° is generally very difficult to peel compared to a test conducted at a peel angle of 180° because the peel angle is lower. In other words, a release film that performs well in a peel test at a peel angle of 30° can be said to have superior releasability compared to conventional release films.

[0069] (2) Evaluation of wrinkle resistance The release film, copper-clad laminate ("NIKAFLEX F-30VC1" manufactured by Nikkan Kogyo) and glass cloth ("116AW" manufactured by Yodogawa Hutec) were set in this order in the RtoR tester, and hot pressing was performed while conveying under conditions of 50 mm / sec, 350 mm / set, and 10 N. The hot pressing conditions were 180°C, 100 gf / cm, 80 sec, and the preheat time was 10 sec. After the hot pressing, the release film in contact with the polyimide surface was observed, and the number of wrinkles of 2 cm or more along the flow direction was visually confirmed. If the number of wrinkles of 2 cm or more was 10 or less, it was evaluated as "○", and if it was more than 10, it was evaluated as "×".

[0070] (3) Evaluation of tracking ability A coverlay film (12.5cm x 12.5cm, polyimide thickness 25μm, epoxy adhesive layer thickness 35μm) with a hole of φ=1mm was laminated on the copper foil surface of a copper-clad laminate (Nikkan Industries "NIKAFLEX F-30VC1": 12.5cm x 12.5cm, polyimide thickness 25μm, copper foil thickness 35μm) so that the epoxy adhesive layer was in contact with the coverlay film. A release film was further laminated so that the release layer a was in contact with the coverlay film. This laminate was heated at 180°C and 30kgf / cm 2 The sample was then heat pressed for 2 minutes under the conditions described above. The release film was then peeled off, and the epoxy adhesive that had flowed out onto the copper-clad laminate (CCL) was observed under an optical microscope. The width of the epoxy adhesive seeping out was measured at 12 points, and the average value was calculated. Based on the measurement results, the conformability of the release film was evaluated as follows. ○: When the average width of the epoxy adhesive seeping out is less than 55 μm ×: When the average width of the epoxy adhesive seeping out is 55 μm or more

[0071] [Table 1]

[0072] [Table 2] [Industrial Applicability]

[0073] According to the present invention, it is possible to provide a release film which has better releasability than conventional ones and can be suitably used in the production of flexible circuit boards by the roll-to-roll method.

Claims

1. A release film having at least one release layer, A release film having a bromine permeability Z of 4 or less as measured by the following bromine-containing adhesive penetration test. (Bromine-containing adhesive penetration test) The adhesive surface of a coverlay film having a bromine compound as an adhesive component is brought into contact with the release layer of the release film, and heat pressed under conditions of a pressure of 30 kgf, 180°C, and 5 minutes. The coverlay film is then peeled off, and the bromine permeability Z is calculated according to the following formula (1). [0010] In formula (1), A(i) and B(i) are the Br and B in the i-th measurement of time-of-flight secondary ion mass spectrometry. - and total fragment intensity, where i is an integer from 1 to 100.

2. 2. The release film according to claim 1, wherein the release layer has an arithmetic mean surface roughness Ra of 0.5 μm or more.

3. 3. The release film according to claim 1, wherein the release layer has an overall crystallinity of 25 to 50%.

4. 4. The release film according to claim 1, 2 or 3, wherein the release layer contains an aromatic polyester resin.

5. 5. The release film according to claim 4, wherein the aromatic polyester resin contains a polybutylene terephthalate resin.

6. 6. The release film according to claim 5, wherein the proportion of polybutylene terephthalate resin in the resin constituting the release layer is 75% by weight or more.

7. 7. The release film according to claim 1, further comprising a cushion layer, and release layers on both sides of the cushion layer.

8. 8. The release film according to claim 1, 2, 3, 4, 5, 6 or 7, which is used in the production of flexible circuit boards by a roll-to-roll method.

Citation Information

Patent Citations

  • Manufacture of laminated printed board

    JP1993283862A

  • Mold release film

    JP2009132806A